Evaluating arrhythmias in ECG signals using wavelet transforms. - Addison, P.S (IEEE Engineering in medicine and biology magazine)
Recent work has attempted to utilize wavelet techniques in the analysis of biomedical signals including ECGs. Here, the authors present an energy-based method of interrogating the ECG in VF using high-resolution, log-scale continuous wavelet plots. With this method, underlying structures within the VF waveform are made visible in the wavelet time-scale half space.